2019
DOI: 10.1039/c8qo01405a
|View full text |Cite
|
Sign up to set email alerts
|

Manganese-mediated reductive amidation of esters with nitroarenes

Abstract: N-Aryl amides were synthesized via the manganese-mediated amidation of esters with nitroarenes without the need for additional catalysts or ligands.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 51 publications
0
36
0
Order By: Relevance
“…Our interest in the development of cost-effective strategy to form amide bonds stems from the consideration of its potential utility in accessing valuable motifs. [31][32][33][34] To avoid the synthesis and purification of reactive metal catalysts, we commenced our studies by using commercially available metal salts as precatalysts for the amidation of ethyl benzoate (1a) with aniline (2a). With our endeavor in the exploration of Cr-catalyzed crosscoupling reactions, 35 we speculated that a reactive low-valent Cr, being formed in situ by reduction with Mg, 36,37 benign CrCl 2 salt was chose as pre-catalyst by the treatment with magnesium in the amidation (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Our interest in the development of cost-effective strategy to form amide bonds stems from the consideration of its potential utility in accessing valuable motifs. [31][32][33][34] To avoid the synthesis and purification of reactive metal catalysts, we commenced our studies by using commercially available metal salts as precatalysts for the amidation of ethyl benzoate (1a) with aniline (2a). With our endeavor in the exploration of Cr-catalyzed crosscoupling reactions, 35 we speculated that a reactive low-valent Cr, being formed in situ by reduction with Mg, 36,37 benign CrCl 2 salt was chose as pre-catalyst by the treatment with magnesium in the amidation (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Thereafter, Cheung and Ma and co-workers reported amidation of aliphatic and aromatic esters 132 with nitroarenes 1 using Mn powder and TMSCl in the absence of any additional ligands or catalyst for preparing amides 133 (Scheme 48). [44] Based on mechanistic study they suggested nitrosobenzene 134 as the possible intermediate participating in the amidation reaction (Scheme 49). TMSCl was essentially required in the process for removing the oxide from surface of Mn and activate the catalyst concomitantly for deoxygenating the nitroarenes.…”
Section: Amidation Of Estersmentioning
confidence: 99%
“…In 2019, Cheung, Ma, and co-workers reported the Mnmediated reductive amidation of alkyl and aryl esters with nitroarenes in the absence of additional catalysts or ligands (Scheme 42). 67 In this approach, they only need TMSCl as additive to reductively couple nitroarenes using Mn as reductant in DMA at 120 °C. This reductive amidation is characterized by a broad substrate scope with respect to both ester and nitroarene partners.…”
Section: Syn Thesismentioning
confidence: 99%